PENCEGAHAN ANEMIA PADA REMAJA PUTRI DI PONDOK PESANTREN DARUSSALAM AL-HAFIDZ KOTA JAMBI - Nurbaiti Nurbaiti (Jurnal Abdimas Kesehatan (JAK), 2019)
Nutritional anemia is a lack of hemoglobin levels in the blood caused by a lack of nutrients needed for the formation of Hb. If a woman who has anemia will be very difficult when she is pregnant and giving birth. This can cause babies born with low weight (less than 2500 grams). In addition, anemia can also result in the death of both the mother and baby during labor. Anemia is one of the health problems throughout the world, especially developing countries. It is estimated that 30% of the world’s population suffer from anemia. The anemia in young women is still quite high. This community service activity will be held at Jambi Jambi Al-Hafidz Pondok Islamic Boarding School. The service method uses survey, lecture, discussion, demonstration / simulation approaches. Problems faced by partners Lack of student knowledge about anemia in adolescents and how to prevent it